Prophylactic implantation of cardioverter-defibrillator in patients with severe cardiac amyloidosis and high risk for sudden cardiac death - Kristen, Arnt; Dengler, Thomas; Hegenbart, Ute; Schönland, Stefan; Goldschmidt, Hartmut; Sack, Falk-Udo; Voss, Frederik; Becker, Rüdiger; Katus, Hugo; Bauer, Alexander (Heart rhythm, 2008)
Background - Cardiac light-chain amyloidosis carries a high risk for death predominantly from progressive cardiomyopathy or sudden death (SCD). Independent risk factors for SCD are syncope and complex nonsustained ventricular arrhythmias. - Objective - The purpose of this study was to test whether prophylactic placement of an implantable cardioverter-defibrillator (ICD) reduces SCD in patients with cardiac amyloidosis. - Methods - Nineteen patients with histologically proven cardiac amyloidosis and a history of syncope and/or ventricular extra beats (Lown grade IVa or higher) received an ICD. - Results - During a mean follow-up of 811 ± 151 days, two patients with sustained ventricular tachyarrhythmias were successfully treated by the ICD. Two patients underwent heart transplantation, and seven patients died due to electromechanical dissociation (n = 6) or glioblastoma (n = 1). Nonsurvivors more often showed progression of left ventricular wall thickness, low-voltage pattern, ventricular arrhythmias (Lown grade IVa or higher), and higher N-terminal pro-brain natriuretic peptide levels than did survivors. Bradycardias requiring ventricular pacing (VVI 40/min <1%, DDD 60/min 6% ± 1%) occurred only rarely. - Conclusion - Patients with cardiac amyloidosis predominantly die as a result of electromechanical dissociation and other diagnoses not amenable to ICD therapy. Selected patients with cardiac amyloidosis may benefit from ICD placement. Better predictors of arrhythmia-associated SCD and randomized trials are required to elucidate the impact of ICD placement in high-risk patients with cardiac amyloidosis.
Gesehen am 21.01.2022